Quantification of nigella sativa oil (NSO) from biodegradable PLGA nanoparticles using FTIR spectroscopy - Doolaanea, Abd Almonem; Harun Ismail, Ahmad Fahmi; Mohamed, Farahidah (Academic Sciences, 2014)
Objective: Quantification of medicinal plant, N. sativa oil, in biodegradable nanoparticles fabricated from PLGA and chitosan was impossible due to the difficulty in the oil extraction-partition method of which the nanoparticle did not dissolve in any solvent.